Implementasi Program Edukasi Ecoprint dalam Meningkatkan Kreativitas dan Kesadaran Lingkungan Anak-Anak - Setyawatiningsih, Sri Catur; Aidil Fiqri Hidayat,; Willy Izazi Putra; Windy Nurdiansa; Wenda Desti Mulia; Junaini Elfadilla; Fadila Fianda; Dela Haria Dinda; Salsa Nabila Putri,; Dwi Latifah; Lily Nurjana; Nelda Wati (LPPM UMRI, 2026)
Supporting the cognitive, motor and imaginative development of preschool and elementary school children through creativity is crucial. At this stage, children are naturally inquisitive and require stimulation through interactive learning activities based on direct experience or hands-on practice. Therefore, the Community Service Programme (KKN) in Teluk Merempan Village, Mempura Subdistrict, Siak Regency, conducted ecoprint training as a creative, environmentally-based learning activity. The aim of this activity is to enhance creativity and instil environmental awareness by using natural materials found in the local area. Participants were first introduced to the concept of ecoprinting, then observed a demonstration of the pounding technique before completing a hands-on practice session using canvas bags. The activity concluded with a qualitative evaluation through observation and interviews. The results showed that participants were able to follow all stages well and produce unique patterns. Around 95% of participants understood the basic concepts of ecoprinting and the production process. The activity was effective in enhancing creativity, critical thinking, fine motor skills, self-confidence and environmental awareness.